Acquired C1 inhibitor deficiency associated with systemic lupus erythematosus affecting the central nervous system. Issue 10 (October 1991) - Nakamura, S; Yoshinari, M; Saku, Y; Hirakawa, K; Miishima, C; Murai, K; Tokiyama, K; Fujishima, M
Abstract : A 22 year old woman with systemic lupus erythematosus affecting the central nervous system had acquired C1 inhibitor deficiency. She was admitted for treatment of psychotic behaviour, but showed no signs of angioedema. The serum complement profile of the patient showed normal C3 concentration and a depletion of C4, C2, C1 inhibitor, and C1q. Her parents had normal complement profiles. An extremely reduced C4 concentration may lead to involvement of the central nervous system in systemic lupus erythematosus.